Can digital governance promote urban energy conservation and emission reduction? A quasi-natural experiment based on "National Pilot Policy of Information Benefiting the People" in China. - Shaohui Zou; Yingying Ji (PLoS ONE)
The digital transformation of government is an important path to achieve the modernization of the national governance system and governance capacity. In recent years, the "National Pilot Policy of Information Benefiting the People" has become a key measure for big data to empower government governance, accelerate the improvement of public service levels and equalization of public services. This paper adopts the difference-in-difference method, takes the "National Pilot Policy of Information Benefiting the People" implemented in my country in 2014 as a quasi-natural experiment of digital governance, and explores the effectiveness of government digital governance measures on urban energy conservation and emission reduction and its potential transmission mechanism based on panel data of 283 cities in China from 2006 to 2021. The study found that the construction of digital government has a positive role in promoting urban energy conservation and emission reduction, and this positive impact is mainly achieved by promoting green technology innovation and strengthening environmental regulation; there are differences in the impact of digital governance on urban energy conservation and emission reduction among cities of different regions, different scales, and different resource endowments. This paper studies the energy conservation and emission reduction effect of government governance from the perspective of digital transformation, and provides important empirical inspiration for the sustainable development of cities under the dual carbon goals and the formulation of energy conservation and emission reduction action strategies.